ANALISIS COMMON SIZE LAPORAN LABA RUGI BANK KALSEL PUSAT PERIODE 2016-2019 - Bella Puspita Rininda; Marliza Noor Hayatie; Muhammad Said (Jurnal Ilmu Ekonomi dan Bisnis, 2021)
Abstract: This study aimed to assess the financial performance of Bank Kalsel using Common Size analysis in the 2016-2019 income statement. The data used was secondary, and the type of data used was quantitative. From the results of the calculation of the Common Size analysis, the financial performance of Bank Kalsel can be said to be entirely satisfactory. Although in some periods it has decreased, it has increased again in the following periods. It means that Bank Kalsel can handle these conditions well and can improve its performance. Keywords: financial performance, financial statements, common size analysis